The Influence of Investment Decisions, Profitability, Company Size and Capital Structure on Company Value in the Pharmaceutical and Cosmetics Sector for the Period 2021-2023 - Eka Susanti; Ickhsanto Wahyudi (Best Journal of Administration and Management, 2025)
This study aims to analyze the effect of investment decisions (PER), profitability (ROA), company size (Ln Assets), and capital structure (DAR) on company value in the pharmaceutical and cosmetics sector listed on the Indonesia Stock Exchange in 2021-2023. In this study, the dependent variable, namely company value, is proxied through Tobin's Q and the independent variables used are investment decisions (PER), profitability (ROA), company size (Ln Assets), and capital structure (DAR). The data population obtained from the annual financial reports is 45 companies from 15 companies selected from the sample using purposive sampling techniques. The data analysis method used is multiple linear regression analysis through the SPSS program. The results of the study show that the investment decision variable has a positive but not significant effect on company value, for profitability and capital structure have a positive effect on company value, but the results for company size have a negative effect on company value, this indicates that there are other factors that are more dominant in influencing company value. Companies that are too large may experience cost efficiency, difficulty adapting to the market and innovation, or the market that provides lower valuations for large companies.